Social Change and Failure. Individual Actions and Systemic Implications - Zotti, Angelo (Italian Sociological Review, 2022)
The hypothesis supported in this paper is that individuals and groups can socialize themselves to negative events in very different, even opposite, ways. The two modes of perceiving and experiencing the failure selected here could be defined in terms of an ‘adaptive failure’ (a failure, even when macroscopic, does not necessarily determine a change of direction: lesson is not learned!) and a ‘strategic failure’ (the failure itself generates social change: trial and error).The aim of this paper is to offer a sociological explanation of these two ways of managing failure, by analyzing: i. the type of social action that is carried out by the agents in these cases; ii. the consequences that these dynamics generate on the physiognomy and structure of socio-cultural systems.The thesis is that an expressive type of action prevails in the first model. Individuals invest emotionally on social situations. This investment usually generates adaptation to the given conditions. As a result, it also adapts to failure. This is because the agents’ true intent is to maximize their advantage in every type of situation. Even in failure. In the second model, one imagines a strategic type of action that tends to achieve predefined goals. In this sense, without prejudice to the final objective, the failure imposes a change of strategy or it may have been planned (and put into account) as a necessary step to achieve the expected result.